2009
DOI: 10.1200/jco.2009.22.0038
|View full text |Cite
|
Sign up to set email alerts
|

Survival Disparities in Patients With Lymphoma According to Place of Residence and Treatment Provider: A Population-Based Study

Abstract: A B S T R A C T PurposeHealth disparities exist according to an individual's place of residence. We evaluated the association between primary area of residence (urban v rural) according to treatment provider (university based v community based) and overall survival in patients with lymphoma and determined whether there are patient groups that could benefit from better coordination of care. Patients and MethodsPopulation-based, retrospective cohort study of 2,330 patients with centrally confirmed lymphoma from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 44 publications
2
38
2
Order By: Relevance
“…Consistent with previous reports 2,25 and potentially due to referral bias, survival of patients cared for at Mayo Clinic was longer than patients in the SEER registry(n=1087) diagnosed with CLL 1999–2004(Figure 3A). For all patients (January 1999 – September 2009), median OS of patients cared for by a CLL hematologist(directly or with fellow) was 10.5 years as compared to 8.4 years(p=0.001) for those cared for by a non-CLL hematologist(directly or with fellow).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous reports 2,25 and potentially due to referral bias, survival of patients cared for at Mayo Clinic was longer than patients in the SEER registry(n=1087) diagnosed with CLL 1999–2004(Figure 3A). For all patients (January 1999 – September 2009), median OS of patients cared for by a CLL hematologist(directly or with fellow) was 10.5 years as compared to 8.4 years(p=0.001) for those cared for by a non-CLL hematologist(directly or with fellow).…”
Section: Resultssupporting
confidence: 90%
“…rural versus metropolitan area; community based versus university-based) may influence survival. 25 While these observations could be due to greater disease-specific expertise among physicians at university and large metropolitan centers, they may simply reflect referral bias or better access to advanced technologies, clinical trials, supportive care, and multidisciplinary support at large centers. Little is known about the direct influence of the hematologist/oncologist’s disease-specific expertise on the outcome of patients cared for in the same practice setting where access to clinical trials, multidisciplinary consultation, and medical technologies are identical.…”
Section: Introductionmentioning
confidence: 99%
“…In the Canadian province of Manitoba, where a similar provincewide cancer control program is in place, a population-based study of all patients undergoing bone marrow transplantation for lymphoma failed to show a survival disadvantage for rural patients [23]. In a population-based, retrospective cohort of 2,330 patients with lymphoma from the U.S. state of Nebraska, patients from rural areas had inferior OS compared with those residing in urban areas [12]. In addition, rural patients treated in Nebraska were less likely to receive SCT as part of their treatment [13,24].…”
Section: Discussionmentioning
confidence: 99%
“…Limited data suggest that rural patients with different lymphoma subtypes may experience adverse outcomes [12][13][14]. Patients with curable aggressive lymphomas, such as diffuse large B-cell lymphoma (DLBCL), could be particularly vulnerable to the effect of place of residence because timely administration of therapy at appropriate dose intensity is considered vital for optimizing outcome.…”
Section: Introductionmentioning
confidence: 99%
“…One study 5 showed that American patients treated by university-based providers were significantly more likely to have a BMT as part of their treatment regimen as compared with patients treated by community-based providers, but did not find a difference between patients from rural and urban areas overall . We investigated this issue in rural and urban Canadians.…”
Section: Introductionmentioning
confidence: 99%